ANALISIS PROFITABILITAS, LIKUIDITAS, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PERUSAHAAN DI BURSA EFEK INDONESIA - Jeslin, Jeslin; Effendi, Syahril (SCIENTIA JOURNAL, 2021)
The fundamental condition of a company can effect the stock price to be cheap or expensive, depending on how the company is performing. If the company is performing well, it will be easy to attract potential investors to invest. This study aims to analyze profitability as measured by the ratio of return on assets, liquidity as measured by the current ratio and earnings per share to stock prices of food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange 2015 to 2019. Using purposive sampling method with 32 companies as population and 10 companies were selected as samples with predetermined criteria. Based on the results of hypothesis testing, it shows that profitability has a partial effect on stock prices. Liquidity does not partially affect stock prices. Earning per share has a partial effect on stock prices. And profitability, liquidity and earnings per share simultaneously affect stock prices. The results of the analysis of the coefficient of determination with an Adjusted R Square of 82% means that profitability, liquidity and earnings per share simultaneously affect the stock price by 82%, while the remaining 18% are other factors that are not included in this study.